Republic of Congo : Enhancing Efficiency in Education and Health Public Spending for Improved Quality Service Delivery for All - World Bank (Washington, DC, 2014)
The development of a wealthier, literate, and healthy society is a fundamental goal of Congo's national development plan (NDP) 2012-16 and poverty reduction strategy paper (PRSP) 2012-16. Appropriate funding allocations and efficient use of funds in education and health are fundamental for the development of the sectors. This public expenditure review (PER) of the Congolese education and health sectors aims at providing inputs to improve efficiency and equity in spending in these sectors. It takes into account the following findings of the macro PER: (i) spending on the social sectors is still low although it has increased over time; (ii) the fiscal space generated by the increased oil revenues has largely boosted investment expenditure; and (iii) budget execution is low which contributes to lower the real level of public spending. The PER is divided in two main parts. Part I, constitutes an overview of the two sector reports. Thus, it presents a brief analysis of the context of the country, a summary of findings of the education and health PER, a discussion on cross-cutting themes on spending in the two sectors, and a summary of recommendations. Part II includes the education and health PER.